2017
DOI: 10.1186/s12879-017-2488-4
|View full text |Cite
|
Sign up to set email alerts
|

Dengue type 4 in Rio de Janeiro, Brazil: case characterization following its introduction in an endemic region

Abstract: BackgroundDue to the populations’ susceptibility, DENV-4 introduction in 2010 led to the occurrence of explosive epidemics in the following years in Brazil. In 2011, DENV-4 was identified in Rio de Janeiro (RJ) and it was prevalent in 2012 and 2013. Here, we aimed to characterize clinical, epidemiological and laboratorial aspects of DENV-4 cases after this serotype introduction in an endemic scenario.MethodsDengue suspected cases (n = 3727) were received and analyzed from January 2011 to December 2013, during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 33 publications
(31 reference statements)
4
30
0
3
Order By: Relevance
“…In 2012, DENV-4 was prevalent and detected in 63% of the cases reported in Brazil [7]. Despite the highest notification in 2013 (1,452,289 cases), DENV-4 circulation was associated with mild cases [8,9], but severe and fatal cases due to DENV-4 were also reported [10]. Although there has been no definitive association of the different DENV serotypes within the clinical course of the disease, it has been suggested that DENV-2 and DENV-3 are more frequently associated with severe disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, DENV-4 was prevalent and detected in 63% of the cases reported in Brazil [7]. Despite the highest notification in 2013 (1,452,289 cases), DENV-4 circulation was associated with mild cases [8,9], but severe and fatal cases due to DENV-4 were also reported [10]. Although there has been no definitive association of the different DENV serotypes within the clinical course of the disease, it has been suggested that DENV-2 and DENV-3 are more frequently associated with severe disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that most patients clinically diagnosed with dengue do not have laboratory-confirmed DENV infections. 13,14 Overall, 126 patients were diagnosed with laboratory-confirmed DF and eight patients were diagnosed with laboratory-confirmed DHF. Sera from select patients (N = 34) were further tested by qRT-PCR for CHIKV RNA, including 20 patients with laboratoryconfirmed DF and four patients with laboratory-confirmed DHF.…”
mentioning
confidence: 99%
“…From 1997 to 2017, 1593 cases of GBS were reported in the state of Rio de Janeiro (annual average, 60 cases). Analysis of monthly GBS cases determined that there were significant increases in GBS from 1 month to the next for 3 years (Farrington test P <0.001): in 2009 (n=115 cases) contemporaneous with the introduction of H1N1; in 2013 (n=85), which coincided with an epidemic of dengue virus type 4; and in 2015 with the arrival of Zika virus (n=326) (Fig. ).…”
Section: Resultsmentioning
confidence: 99%